Pemaknaan Kebahagiaan oleh Remaja Broken Home - Sarah Hafiza; Marty Mawarpury (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2018)
Happiness is the expectation for every person including teenager. However, parental divorce may have impact on teenagers’ happiness. The aim of this study is to know happiness in teenager whose parents divorced. Data for this research were obtained using qualitative method with case study design. Subject was selected using purposive sampling technique. The respondent was a male teenager with divorced parents. Data collection was carried out through interview. The results showed that the respondent had three aspects of happiness are life is pleasant, meaningful, and engaging.